The Dolphy-lipino people analyzing the Dolphy icon and the potrayals of Filipino culture - Hermonio, Ella Jane G. 1993- (2013)
"This undergraduate thesis analyzes the representation of Filipino culture in the comic portrayals of Rodolfo Vera Quizon, alson known as Dolphy. Due to the amplified campaign for his conferment of the title of National Artist after his recent death, his contributions to the "cultural heritage of the country" and "national cultural identity" need to be examined. The nature of the comedy genre is seen to be so complex, where messages can be implied and interpreted in various ways. This research, through structural textual analysis, studies the television shows and films of Dolphy on how he personified Filipino beliefs and behavior. Moreover, this study recognizes the power and influence possessed by the iconography of Dolphy. The funny and relatable personas he took on facilitated how he communicated and perpetuated negative cultural practices to the audiences. The State further contributes to the institutionalization of Dolphy as an ideological state apparatus through the National Artist Award. Therefore, Dolphy is legitimately instated as a significant model for the Filipinos. For the better or otherwise, this scheme makes the people aspire to imitate his fictional, as well as real-life, narratives."